THE IMPACT OF ORGANIZATION DESIGN ON WORK PERFOMANCE OF COOPERATIVE DEPARTMENT, SMALL AND MEDIUM ENTERPRISES BUSINESS OF TRADE IN BANDUNG CITY - Imas Sumiati; Yayan Mulyana; Tine Ratna Poerwantika (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2018)
Based on the result of research in the Cooperative Office, Micro, Small and Medium Enterprises Bandung and the Department of Trade and Industry Bandung, there is work performance that has not been maximized, it can be seen from the indicators: the quantity of work, job knowledge and personal quality. This is due to: the complexity and formalization that have not been optimize. This research used combination research method by using Sequential Model that is with data and quantitative data analysis in first stage and with qualitative data in second stage. Technique collective data consist of literature study, field study (participant and non-participant observation, in-depth interviews with two heads of service, questionnaires distributed to 28 persons, Division Head and Section Head of both Focus Group Discussion), research design, data and data sources, key informant and informant, and documentation studies. The result of this research is quantitative result of 68.9% result of organizational design on work performance in Cooperation Department, Micro, Small and Medium Enterprises, Trade and Industry Office of Bandung City that have a high enough influence. The result of qualitative research is micro business that became a municipality affair then small enterprises are provincial affairs, and medium enterprises are the affairs of central government. This showed that there are still overlapping in work specialization and the authority that has not optimize yet from central to region, thus it needs a new concept or research findings that will certainly enrich organizational theory and study related to organizational structure and public institutional related to work performance. Keywords: Organizational Structure, Work Performance, New SOTK.